CURRENT SOLUTIONS TO PROBLEMS IN THE TREATMENT OF GIANT POSTOPERATIVE HERNIAS (World Bulletin of Public Health, 2023)
The article presents the data of studies of the last 15 years on surgical treatment of giant postoperative hernias of the anterior abdominal wall. The latest achievements of laparoscopic and robotic surgery in this direction, as well as modifications of open methods with separation of transverse abdominal muscle components are indicated. The authors described both positive sides and disadvantages of each method. Unresolved problems are highlighted, ways to improve the results of surgical treatment of this complex pathology are outlined.
Keywords: giant postoperative hernias; laparoscopy; abdominal wall; nanotechnology